The Development of My Set Induction Skill through Video Self-Reflection: A Self-Reflective Research: set induction skill - Fatinah, Dwi Oryza; Setyono, Budi; Sukmaantara, I Putu (English Education Study Program, 2022)
Researching my set induction skill during teaching practicum program is essential because it is the crucial step that could determine the success of teaching and learning process. Interesting set-induction could help students focus on the topic to be learned, connect their prior knowledge with the new topic, and motivate them learn the materials. In this research, I did self-reflective study on how I developed my set-induction skill. I accomplished this research by videotaping my teaching performance, and continued by writing self-reflective journal based on the video. I analyzed the data using thematic analysis. The analysis revealed 5 themes, i.e., gaining students’ attention, building students’ motivation, assessing students’ prior knowledge. providing content overview, and determining students’ expectation. It is suggested that teachers videotape their teaching performance and do critical reflection based on the recorded video to plan better teaching performance.